In vitro evaluation of cytotoxicity of Emblica officinalis (amla) on cultured human primary dental pulp fibroblasts - Bulbule, Aditi; Mandroli, Praveenkumar; Bhat, Kishore; Bogar, Chetna (Journal of the Indian Society of Pedodontics and Preventive Dentistry, 2019)
Context: The dental pulp tissue is capable of healing after surgical amputation of infected/inflamed tissue during vital pulp therapy, when in contact with a suitable medicament. Emblica officinalis (amla), a traditional medicine, is one such medicament which has never been evaluated for its healing potential in pulp therapy. Aims: The aim of the study was to evaluate the cytotoxicity of E. officinalis (amla) against human primary dental pulp fibroblasts. Settings and Design: This was in vitro study. Subjects and Methods: Human dental pulp fibroblasts were obtained from dental pulp tissue of extracted over-retained primary incisors. The primary cells were cultured using the Dulbecco's Modified Eagle's Medium and used for the study after the fourth passage. The test medicament was E. officinalis with mineral trioxide aggregate (MTA) (100%) and untreated cells as positive and negative controls, respectively. Methyl-thiazol-diphenyl-tetrazolium (MTT) cytotoxicity assay was performed, and the cell survival was observed and analyzed at intervals of 24, 48, and 72 h. Statistical Analysis Used: Cell survival within groups was compared with Wilcoxon matched-paired t-test and in between groups at each point interval was analyzed with the Kruskal-Wallis ANOVA test. The level of significance was set at 0.05. Results: Within the groups, across the time periods of evaluation, there was a decline in cell survival in both the groups but was statistically significant in the MTA group. On interval-wise comparison, the decline in cell survival was statistically significant between the three groups at 72 h (P = 0.001). Conclusions: E. officinalis preserved the vitality of the human primary dental pulp fibroblasts and has the potential to be developed into vital pulp therapy medicament.